Kościół jako sakrament nadziei w czasach dewaluacji słowa - Nadbrzeżny, Antoni (Verbum Vitae, 2025)
The aim of this article is to present the Church as a sacrament of hope in the context of the cultural phenomenon known as global logorrhea. This term denotes an uncontrolled stream of ambivalent words, often semantically devalued, which contribute to the alienation of contemporary humanity. Logorrhea gives rise to the danger of existential despair and calls for an adequate theological response. For this reason, contextual ecclesiology seeks to portray credibly the Incarnate Word of God as the transcendent source of the Great Hope. The Church, as the sacrament of the risen Christ present in the history of the world, inevitably clashes with the onslaught of new ideological proposals of a utopian nature. These emerge as the effect of dynamic logorrhea which, following the collapse of former relatively coherent social utopias, continues to generate utopian syncretisms based on an arbitrary combination of words and ideas torn from their original contexts. In the face of this phenomenon, an important task of ecclesiology is both the critique of emerging utopias and the rational justification of the thesis that Christianity, in its very essence, is not a utopia. The article employs the theological method of correlation, appropriate to contextual and pretextual ecclesiology, and is divided into five parts. The first characterizes the phenomenon of logorrhea. The second develops a typology of the human word. The third discusses the significance of the ecclesial making-present of the Incarnate Logos in the face of existential despair. The fourth reveals the reasons for the seductive power of utopia. The fifth demonstrates the liberating power of Christ as the Great Hope and explains why Christianity is not a utopia.